Organizational antecedent with job satisfaction, work performance as mediators and knowledge sharing practices among academician at Malaysia research universities - Abdullah, Nurfarahin Jasmine See; Ismail, Ismi Arif; Idrus, Khairuddin (EconJournals, 2015)
The survey of this inquiry is to define the relationship between organizational antecedent, job satisfaction, work performance as mediators and knowledge sharing practice among academician at Malaysia Research Universities. The hypothesis for this research are organizational antecedent has a relationship with job satisfaction and work performance as well has relationship with knowledge sharing practice. The variables in this research are organizational antecedent which consist of people, organization and technology, well of knowledge sharing practice consist of socialization, externalization, combination and internalization. For mediators that are job satisfaction consist of job, salary, promotion, supervision and co-worker and work performance consist of work, ability, discipline, relationship, and innovation. Using the theory of multiple perspective for organizational antecedent, theory of needs for job satisfaction and work performance and for knowledge sharing practice SECI. The data analysis measured this research were quantitative and for structural equation modelling there structural model. The findings of this research support the hypothesized relationship proposed and the results of mediators for job satisfaction and work performance towards the relationship of organizational antecedents and knowledge sharing practice. This research served to prepare a segment in a more inclusive global picture of independent variable that organizational antecedent, mediator variables that job satisfaction and work performance and dependent variable that knowledge sharing practice.